Universal Mental Health Screening in California School Settings: Current Practices, Barriers, and Opportunities - Stephanie A. Moore; Samira Soleimanpour; Sara Geierstanger; Jessica Yu; Eric M. Davidson; Kali Patterson (Contemporary School Psychology, 2026)
Abstract When implemented as part of a multi-tiered system of support, universal mental health screening (UMHS) can facilitate early identification and data-based decision-making in support of students’ social, emotional, behavioral, and mental health needs. Despite increasing interest in school-based UMHS, its widespread uptake has historically been stagnant. Recent national estimates indicate that rates of UMHS implementation are increasing; however, the information available about current practices, as well as the barriers or facilitators that affect adoption and implementation, remain limited. As part of a legislative budget initiative in California, the study authors conducted a statewide survey of local education agency representatives to describe current UMHS practices, including the barriers and facilitators that may influence adoption and implementation. Half (51%) of respondents ( N = 155), who represented 51 of California’s 58 counties, indicated that their site was conducting UMHS; however, participants endorsed a wide range of screening practices. Nearly all participants agreed that conducting UMHS would benefit their students, staff, and school communities; yet, among participants whose sites were or were not conducting UMHS, the most prevalent barriers reflected service system capacity issues, including insufficient resources to support students’ mental health needs. Facilitators identified by participants suggest that building school or district capacity (e.g., by addressing staff shortages or providing professional development) and supportive infrastructure (e.g., by allocating time in school calendars or daily schedules) may benefit UMHS adoption and implementation. Together, our findings emphasize the importance of integrating UMHS within multi-tiered school mental health systems and provide support for additional and sustained investments in these initiatives.